Erres - Sioui Durand, Guy (CV Photo)

(untitled) (Les Productions Ciel variable, 2000)
Summary A double artistic meaning is superimposed on the notion of landscape: invented images and real cultural territories. Adopting horizontality as a visual point of reference, Civilisation by Quebecer Ivan Binet and Cold City Frieze by Iroquois Jeffrey Thomas wander nomadically through this paradigm of identity. The "wanderings" of the postmodern woodsman and the Native in the City work in tandem.